2019
DOI: 10.3390/foods8080320
|View full text |Cite
|
Sign up to set email alerts
|

Egg Yolk Antioxidants Profiles: Effect of Diet Supplementation with Linseeds and Tomato-Red Pepper Mixture before and after Storage

Abstract: This study evaluated the effect of dietary incorporation of linseed alone or along with dried tomato paste-pepper powder mix on egg physical characteristics, antioxidant profiles, lipid oxidative status, and yolk coloration before and after storage at 4 °C for one month. Sixty Novogen White laying hens, 27 weeks-old, were divided into three groups and given 100 g/hen/day of a standard diet (C), standard diet containing 4.5% of ground linseed (L), linseed diet containing 1% of dried tomato paste and 1% of sweet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 88 publications
5
52
0
3
Order By: Relevance
“…In this respect, literature is very scarce, making it di cult to compare our results. A study by Omri et al [30], found no changes in avonoids content of hens' egg yolk supplemented with linseed alone or combined with dried tomato-red pepper mixture before and after storage, is close to our ndings. Omri and Abdouli [37], however, reported an increase in the avonoid concentration of egg yolk (1.53 to 2.96 mg CAE/g) and (1.53 to 3.02 mg CAE/g) with hens supplemented with sweet pepper and dried tomato and fenugreek seeds.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this respect, literature is very scarce, making it di cult to compare our results. A study by Omri et al [30], found no changes in avonoids content of hens' egg yolk supplemented with linseed alone or combined with dried tomato-red pepper mixture before and after storage, is close to our ndings. Omri and Abdouli [37], however, reported an increase in the avonoid concentration of egg yolk (1.53 to 2.96 mg CAE/g) and (1.53 to 3.02 mg CAE/g) with hens supplemented with sweet pepper and dried tomato and fenugreek seeds.…”
Section: Discussionsupporting
confidence: 91%
“…Studies on the Se supplementation (inorganic or organic) on the egg yolk colour are lacking. However, regarding the calorimetric determination, a report by Omri et al [30] revealed a decreased (p < 0.05) in the lightness of yolk colour with 2% tomato and red pepper mixture supplementation. Dietary addition of 130 g of dried tomato peel per kg was reported to enhance the egg yolk colour index from 8.5 to 14.6 [37].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies on evaluation of beneficial effects of nutraceuticals in vitro [12] and in vivo [13] models have been presented, in particular dietary supplementation studies in animal [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Лютеин -основной пищевой каротиноид, предотвращающий дегенерацию макулы при старении, улучшающий когнитивные функции, состояние сердечно-сосудистой системы, уменьшающий риск развития рака (17,18) и обладающий противовоспалительным действием (19). Для обогащения продукции птицеводства каротиноидами в кормлении птицы часто используют либо натуральные порошки из высушенных томатов (20) и/или красного перца (21), травяные добавки, например экстракт цветков календулы (4), микроводоросль спирулину (22), либо каротинсодержащие препараты, полученные из растительного сырья (12,23,24).…”
unclassified